2018
DOI: 10.1111/tid.12914
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intravenous or intravesical cidofovir in the treatment of BK polyomavirus‐associated hemorrhagic cystitis following adult allogeneic stem cell transplantation—A systematic review

Abstract: There is only weak evidence for the use of CDV. The intravesical admission route should be further investigated because of a good toxicity profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 31 publications
(91 reference statements)
2
17
0
2
Order By: Relevance
“…Here, cidofovir was studied extensively; however, it is very nephrotoxic itself. Therefore, application in patients who already suffer from kidney failure is not reasonable [ 23 ]. Our results suggest that targeting the immune response to BKPyV might be a promising approach for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Here, cidofovir was studied extensively; however, it is very nephrotoxic itself. Therefore, application in patients who already suffer from kidney failure is not reasonable [ 23 ]. Our results suggest that targeting the immune response to BKPyV might be a promising approach for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 30% of non-kidney transplant paediatric patients receiving intravenous cidofovir for adenovirus infections developed nephrotoxicity and the risk appears to be dose dependent [5]. Up to 50% of patients develop nephrotoxicity when intravenous cidofovir is used in haematopoietic stem cell transplant patients [6]. In our review (Supplementary data), 3 of 13 kidney transplant recipients (23.1%) developed worsening of renal function after the administration of intravenous cidofovir for adenovirus infections and 5 cases (38.5%) had a >30% increase in serum creatinine from baseline after the completion of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Intravesical cidofovir has also been used for the treatment of polyomavirus-associated haemorrhagic cystitis in haematopoietic stem cell transplant patients. In a systematic review, intravesical cidofovir was found to be more effective and have a lower risk of nephrotoxicity than intravenous cidofovir [6].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is only weak evidence for the use of cidofovir as an in vivo anti-BKV drug. 16 Also, the pronounced nephrotoxicity limits its use particularly in renal transplantation. 10 In addition, cidofovir-resistance has been noted for multiple viruses.…”
Section: Introductionmentioning
confidence: 99%